2016
DOI: 10.1002/14651858.cd010815.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Assistive devices, hip precautions, environmental modifications and training to prevent dislocation and improve function after hip arthroplasty

Abstract: Very low quality evidence is available from single trials, thus we are uncertain if hip precautions with or without the addition of equipment and functional restrictions are effective in preventing dislocation and improving outcomes after THA. There is also insufficient evidence to support or refute the adoption of a postoperative community rehabilitation programme consisting of functional reintegration and education compared to conventional rehabilitation strategies based on functional outcomes.Further high-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 58 publications
1
40
0
Order By: Relevance
“…A systematic search of the available evidence led to the identification and inclusion of 1 guideline (GL), 8 systematic reviews (SRs), and 5 randomised controlled trials (RCTs) (see Figure 1). The overall quality assessment of the SR is between low (Di Monaco et al, 11 Wijnen et al, 12 Wu et al 13 ) and moderate (Hoogeboom et al, 14 Hansen et al, 15 Minns Lowe et al 16 ) confidence intervals with only 2 SRs occupying the extreme categories (high confidence for Smith et al 17 2014 and the critically low confidence for Lemney et al 18 ). According to the inclusion criterion of the PEDro score > 6/10, all RCTs show a moderate quality with 2 RCTs scored at 6/10 (Matheis et al, 19 Winther et al, 20 ), 2 at 7/10 (Huang et al, 21 Vesterby et al 22 ) and 1 at 8/10 (Busato et al 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…A systematic search of the available evidence led to the identification and inclusion of 1 guideline (GL), 8 systematic reviews (SRs), and 5 randomised controlled trials (RCTs) (see Figure 1). The overall quality assessment of the SR is between low (Di Monaco et al, 11 Wijnen et al, 12 Wu et al 13 ) and moderate (Hoogeboom et al, 14 Hansen et al, 15 Minns Lowe et al 16 ) confidence intervals with only 2 SRs occupying the extreme categories (high confidence for Smith et al 17 2014 and the critically low confidence for Lemney et al 18 ). According to the inclusion criterion of the PEDro score > 6/10, all RCTs show a moderate quality with 2 RCTs scored at 6/10 (Matheis et al, 19 Winther et al, 20 ), 2 at 7/10 (Huang et al, 21 Vesterby et al 22 ) and 1 at 8/10 (Busato et al 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…Except in two cases where the authors had changed this to major and minor outcomes and to main and secondary outcomes but there was no explanation in the review why this had been changed. [20,21] In one other review there was no name and again in another review the outcomes were just named "outcomes of interest".…”
Section: Item Surveyedmentioning
confidence: 99%
“…Four systematic reviews (Barnsley et al, 2015;Sharma et al, 2009;Smith et al, 2016;van der Weegen et al, 2016) and a literature review (Tejwani and Immerman, 2008) have all concluded that hip precautions are not needed when an anterolateral surgical approach is used. The reviews support the suggestion that hip precautions provide no additional benefit with regard to reducing dislocation rates and, moreover, are associated with slower return to activities, significant expense, and decreased patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Also, extensive discussions with staff suggest that, in practice, they would find an RCT impossible to administer as they work across wards. Moreover, the number of participants required to demonstrate a difference between hip precautions and no hip precautions would be very large; previous studies that have focused on the rate of dislocation as the primary outcome have been underpowered (Coole et al, 2013;Smith et al, 2016). A multicentre clustered RCT is not currently feasible; we have previously discussed conducting a multicentre RCT with several hospitals, but they were not willing to participate.…”
Section: Introductionmentioning
confidence: 99%